Acailandica and Ipamerica: two new Neotropical grapholitine genera (Lepidoptera: Tortricidae) - Razowski, Józef; Becker, Vitor O. (Zootaxa, 2016)
Two genera, Acailandica and Ipamerica, and five species (Acailandica acailandiae, A. maja, A. hilara, A. cacaulandiae, Ipamerica auctuncus) are described as new. Species of Acailandica are brightly colored (= telochromatic), whereas those of Ipamerica are cryptic. Carpocapsa comptana Walker, Grapholitha subtilana Zeller, and Laspeyresia pyrozona Meyrick are transferred to Acailandica, resulting in the following new combinations: Acailandica comptana (Walker), A. subtilana (Zeller), and A. pyrozona (Meyrick).